Climatic sensitivity in the Algerian steppes: Drought indices and remote sensing - Youb, Okkacha; Boultif, Meriem; Bourfa, Said; Farhi, Yassine; Faci, M.; Djoudi, W.; Oubadi, M. (Technium Social Sciences Journal, 2022)
These last years, the Algerian steppe has known a strong degradation caused in particular by the scarcity of the annual rainfall. It spreads in certain cases to successive years generated by a persistent drought. A series of indices were applied to rainfall records recorded for 30 years (1985-2015) in the treated stations to identify the severity of the drought in the steppe regions. The present work proposes to study and compare the performance of some drought indices to identify a permanent monitoring system in the steppe. The indices studied are Pluviometric Deficit Index (PDI), StandaPDIzed Precipitation Index (SPI), and the Ratio compared to the Normal (RN). We can deduce Climate variability is manifested by regressive spatio-temporal dynamics, thus, drought is recurrent phenomenon in the Algerian steppe